The relationship between sales promotions and online impulse buying in Malaysia - Shahida Shabi, Muhammad Asyraf Hasim, Mohd Farid Shamsudin, Aeshah Mohd Ali, (Opción, 2019)
The aim of this study is to examine sales promotion as a factor that gives impact on online impulse buying among Malaysians. The study was conducted utilizing the survey research method, aiming to create a better understanding of online impulse buying behaviour. The results show that sales promotion affect online impulse buying behaviour among online consumers in Malaysia. The conclusions showed that sales promotions positively impacted online impulse buying behaviour. These findings are expected to assist online retailers to give more focus on developing better and more creative sales promotions programs.